Geometrical correction and geo-referencing for automatic map data entry - Tạo, Ngô Quốc (Journal of Computer Science and Cybernetics, 2016)
This paper presents the method of Geometrical Correction and Geo-referencing for Automatic Map Data Entry. We propose the method to find linear and polynomial transformations. We transform relative coordinate system maps vectorized into maps of projection coordinate systems. Be side, we use this method to merge two pages of an image (a map) into a page. The paper also present the selecting most appropriate projection-best fitting. This technique is implemented in the software packages MapScan and POPMAP. This technique is applied to maps such as topography, hydrography, transportation, satellite maps, etc.. Besides it is also used for geometrical correction of technical drawings, electronic circuits, fingerprints, etc..